2021
DOI: 10.1038/s41598-021-81469-0
|View full text |Cite
|
Sign up to set email alerts
|

Mitofusin-2 modulates the epithelial to mesenchymal transition in thyroid cancer progression

Abstract: Here, we investigated the potential roles of Mitofusin-2 (MFN2) in thyroid cancer progression. MFN2 regulates mitochondrial fusion/division in cells and plays an important role in various aspects of cell metabolism. MFN2 might involve in cell cycle regulation, apoptosis, and differentiation, and it might play a role as a tumor suppressor in carcinogenesis. We evaluated the prognostic impacts of MFN2 expression in thyroid cancer by analyzing TCGA data. In vitro and in vivo, MFN2 was knocked out using CRISPR/Cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…8 ). The role of mitochondrial dynamics mediated by DRP1 and MFN2 in migration of ovarian cancer cells is consistent with the previous studies 47 , 48 . It was reported that mitochondrial fission regulated the migration of malignant oncocytic thyroid tumor cells, breast cancer cells and lung cancer cells 49 - 51 .…”
Section: Discussionsupporting
confidence: 92%
“…8 ). The role of mitochondrial dynamics mediated by DRP1 and MFN2 in migration of ovarian cancer cells is consistent with the previous studies 47 , 48 . It was reported that mitochondrial fission regulated the migration of malignant oncocytic thyroid tumor cells, breast cancer cells and lung cancer cells 49 - 51 .…”
Section: Discussionsupporting
confidence: 92%
“…The direct interaction between miR-93 and 3 -UTR of FBXO31 was experimentally validated in several breast cancer cell lines by Manne et al (2017) . Another prostate cancer-specific target of miR-93, MFN2, was shown to suppress breast and thyroid cancer progression through AKT signaling ( Xu et al , 2017 ; You et al , 2021 ). The direct binding of miR-93 to 3 -UTR of MFN2 was also experimentally validated with luciferase reporter assays ( Feng et al , 2019 ; Zhang et al , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The direct interaction between miR-93 and 3’-UTR of FBXO31 was experimentally validated in several breast cancer cell lines by Manne et al [44]. Another prostate cancer-specific target of miR-93, MFN2, was shown to suppress breast and thyroid cancer progression through AKT signaling [45, 46]. The direct binding of miR-93 to 3’-UTR of MFN2 was also experimentally validated with luciferase reporter assays [47, 48].…”
Section: Discussionmentioning
confidence: 99%